Influence of Cubosome Surface Architecture on Its Cellular Uptake Mechanism - Deshpande, Sonal (Langmuir : the ACS journal of surfaces and colloids, 2017)
Interaction of nanoparticles with biological systems is a key factor influencing their efficacy as a drug delivery vehicle. The inconsistency in defining the optimal design parameters across different nanoparticle types suggests that information gained from one model system need not apply to other systems. Therefore, selection of a versatile model system is critical for such studies. Cubosomes are one of the potential drug delivery vehicles due to their biocompatibility, stability, ability to carry hydrophobic, hydrophilic, and amphiphilic drugs, and ease of surface modification. Here we report the importance of surface architecture of cubosomes by comparing their cellular uptake mechanism with poly-ε-lysine (PεL)-coated cubosomes. Uncoated cubosomes entered cells by an energy-independent, cholesterol-dependent mechanism, whereas PεL-coated cubosomes relied on energy-dependent mechanisms to enter the endosomes. As endosomal entrapment was evaded by uncoated cubosomes, they can be preferably used for cytosolic delivery of therapeutic agents